FUNGSI BADAN PEMBERDAYAAN PEREMPUAN PERLINDUNGAN ANAK DAN KELUARGA BERENCANA (BPPPAKB) PROVINSI RIAU DALAM PELAKSANAAN INSTRUKSI PRESIDEN NO. 9 TAHUN 2000 TENTANG PENGARUSUTAMAAN GENDER DALAM PEMBANGUNAN NASIONAL - Maharani Yas; Tuti Khairani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The BPPPAKB is one of the leading institution of Riau Province in realizing justice and gender equality in all development in Riau Province. The application of the gender mainstreaming is instructed to all ministries of national government. The aim of this research is to know and analyze the function and factors which influence the BPPPAKB of Riau province in executing the Presidential Instruction No. 9 Year 2000 About Gender Mainstreaming In National Development. The result of this research show that the function of BPPPAKB of Riau province in executing that presidential instruction is not maximal yet. From the data it can be seen that there wewe a gap in fulfiling the basic right between male and female also, it ca be clearly seen that some of government buildings are gender bias meanwhile, the factors that influence the BPPPAKB of Riau province in executing that presidential instruction were the existanc of patrialism culture in our society, especially on those who took policy; weak socialization about gender mainstreaming from the chairperson to the staff, the existence of ego sectoral; disaggregated data; and the stereotype that gender mainstreaming is identical to the female. Last, the lack of chairpersons commitment to realize the gender mainstreaming.Key word: function, gender mainstreaming